2007
DOI: 10.5194/npg-14-799-2007
|View full text |Cite
|
Sign up to set email alerts
|

Investigating turbulent structure of ionospheric plasma velocity using the Halley SuperDARN radar

Abstract: Abstract. We present a detailed analysis of the spatial structure of the ionospheric plasma velocity in the nightside Fregion ionosphere, poleward of the open-closed magnetic field line boundary (OCB), i.e. in regions magnetically connected to the turbulent solar wind. We make use of spatially distributed measurements of the ionospheric plasma velocity made with the Halley Super Dual Auroral Radar Network (SuperDARN) radar between 1996 and 2003. We analyze the spatial structure of the plasma velocity using str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 32 publications
7
47
0
Order By: Relevance
“…Several recent publications focused on the electric field fluctuations in the same region (Abel et al, 2006(Abel et al, , 2007Parkinson, 2006Parkinson, , 2008. Although the scaling exponents reported in these papers describe a different aspect of auroral complexity, they can be reconciled with our analysis assuming that the electric field and the emission intensity fluctuations are generated by the same physical phenomenon.…”
Section: Discussionsupporting
confidence: 64%
“…Several recent publications focused on the electric field fluctuations in the same region (Abel et al, 2006(Abel et al, , 2007Parkinson, 2006Parkinson, , 2008. Although the scaling exponents reported in these papers describe a different aspect of auroral complexity, they can be reconciled with our analysis assuming that the electric field and the emission intensity fluctuations are generated by the same physical phenomenon.…”
Section: Discussionsupporting
confidence: 64%
“…It has been found that the scale-free spatial structure of the ionospheric velocity fluctuations measured by the Halley SuperDARN radar between 45 km up to about 1000 km is characterised by different values of power law exponents in areas of open and closed magnetic field lines (Abel et al 2006(Abel et al , 2007. At the same time, analysing the scaling features of the electric field fluctuations on scales of 0.5-256 km at various altitudes over the auroral zone and polar cap some authors have not found significant differences (Golovchanskaya et al 2006;Golovchanskaya and Kozelov 2010), suggesting that the drivers of turbulence in the two regions probably have the same nature.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the TIGER radar data were conditioned in the same way as Abel et al (2007). The results obtained, combined with those of Parkinson (2006), imply that especially for TIGER Population B, there was reasonable conformity to power law scaling from τ =8 s (and possibly less) to ∼256 min (and greater?).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Furthermore, the α-spectra quantified the variation of the scaling properties with temporal scale, whereas the complementary "rank-order multifractal spectrum" recently proposed by Chang and Wu (2008) evaluates the variation of scaling properties with event size. Abel et al (2007) reported the results of a structure function analysis of spatial fluctuations in ionospheric plasma velocities measured using the Halley SuperDARN radar. They presented a thorough discussion on the effects of data conditioning.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation